Design, Synthesis and In Vivo Fluorescence Imaging Study of a Cytochrome P450 1B1 Targeted NIR Probe Containing a Chelator Moiety. (30th May 2022) - Wang, Zengtao; Chen, Dongmei; Fan, Qiqi; Wu, Zhihao; Dong, Jinyun; Cui, Jiahua; Wang, Jie; Xu, Ting; Meng, Qingqing; Li, Shaoshun
Abstract: Cytochrome P450 (CYP) 1B1 has been found to be overexpressed specifically in tumor tissues at an early stage, which makes it a potential cancer biomarker for molecular imaging. Multimodal imaging combines different imaging modalities and offers more comprehensive information. Thus, imaging probes bearing more than one kind of signal fragment have been extensively explored and display great promise. Herein, we developed a near infrared (NIR) probe with a chelator moiety targeting CYP1B1 by conjugating α‐naphthoflavone (ANF) derivatives with both an NIR dye and a chelator for potential application in bimodal imaging. Enzymatic inhibitory studies demonstrated inhibitory activity against CYP1B1 and selectivity among CYP1 were successfully retained after chemical modification. Cell‐based saturation studies indicated nanomolar range binding affinity between the probe and CYP1B1 overexpressed cancer cells. In vitro competitive binding assays monitored by confocal microscopy revealed that the probe could specifically accumulate in tumor cells. In vivo and ex vivo imaging studies demonstrated that the probe could effectively light‐up the tumor tissues as early as 2 hours post‐injection. In addition, the fluorescence was significantly blocked by co‐injection of CYP1B1 inhibitor, which indicated the probe accumulation in tumor sites was due to specific binding to CYP1B1. Abstract : A near infrared (NIR) probe with a chelator moiety targeting CYP1B1 was developed by conjugating α‐naphthoflavone (ANF) derivatives with both an NIR dye and a chelator for metal labelling. This probe could be a promising tool for the detection of tumors and for studying the expression of CYP1B1 during tumorigenesis.alpha‐naphthoflavone derivativeschelatorcytochrome P450 1B1 enzymemolecular imaging, NIR probes